Older age and higher parity are associated with nonuse of the partograph at Mbarara Regional Referral Hospital, Uganda - Lugobe, Henry Mark; Kanyesigye, Hamson; Mpiima, Derrick; Ssemujju, Augustine; Masinda, Abraham; Mulisya, Olivier; Twizerimana, Hillary; Bajunirwe, Francis; Mugyenyi, Godfrey (International Journal of Gynecology & Obstetrics, 2019)
A retrospective review of medical records from mothers admitted to MRRH's postnatal ward between October 2016 and March 2017. Partograph use and whether it had been completed to standard were analyzed.Of 527 study participants, 409 (77.6%) records contained a partograph, of which only 17 (4.2%) had been completed to standard. Parameters most commonly completed to standard were monitoring of cervical dilatation (n=41, 10%), fetal heart rate (n=21, 5.1%), and uterine contractions (n=18, 4.4%). Age older than 30 years (prevalence ratio 1.73; 95% CI, 1.14–2.64) and parity greater than or equal to five (prevalence ratio 1.88; 95% CI, 1.19–2.98) were associated with nonuse of the partograph. Birth outcome was recorded in 98.8% (n=404) of partographs.Appropriate use of the partograph to monitor mothers in labor was extremely low; most common use was to record birth outcomes. Older mothers and those with higher parity were less likely to have their labor monitored using a partograph and should be targeted for partograph interventions.
Keywords: Partograph; Uganda; Use